Surface Temperature Distribution Through Vegetation Density and Building growth in Makassar City - Andrew Stefano; Sri Endayani (Jurusan Pertanian Politeknik Pertanian Negeri Samarinda Kampus Sei Keledang Jalan Samratulangi, Kotak Pos 192 Samarinda 75123, 2024)
The high temperature phenomenon is an event where the temperature in the city area is hotter than the surrounding area. Indonesia is located in a tropical climate, so several cities have the potential for temperatures to rise during the dry season. The city of Makassar is one of the cities with a high level of urbanization. With residents' enthusiasm for looking for work in the city, the land around the city has been converted into built-up land. Conditions like this make the existence of green open space uneven. This research aims is to determine the distribution of high-temperature phenomena through a spatial approach using remote sensing technology and geographic information systems. This research uses Landsat imagery for 2022 with the Land Surface Temperature (LST), Normalized Difference Vegetation Index (NDVI), and Normalized Difference Built-up Index (NDBI) methods. The results of the research explain that the large number of existing buildings has caused an increase in urban temperatures, from an initial temperature of 29.93 oC to 39.51 oC.The increase in temperature occurs throughout the year, with the hottest peak temperature reaching 37 oC on April 15, 2022. The condition of vegetation density decreased by 0.05, starting from 0.66 in 2012 to 0.61 in 2022; this is in line with the increase in building area to 15,368 ha in 2022. This condition makes Makassar City one of the hottest cities in Indonesia. With an increasingly high need for built-up land and high mobility, it has the potential to accelerate temperature changes, so it is necessary to provide green open space in densely built areas by creating public open spaces. open private.